The effectiveness of a fall detection device in older nursing home residents: a pilot study - TUFAN ÇİNÇİN, ASLI; AFŞAR FAK, NAZİRE EFSER YEŞİM; TAZEGÜL, GÖKHAN; FAK, ALİ SERDAR (My University, 2024)
Background: Real-world research to evaluate the effect of device technology in preventing fall-related morbidity is limited. This pilot study aims to investigate the effectiveness of a non-wearable fall detection device in older nursing home residents. Methods: The study was conducted in a nursing home with single-resident rooms. Fall detection devices were randomly set up in half of the rooms. Demographic data, comorbidities, lists of medications, and functional, nutritional, and frailty status were recorded. The residents were followed up for 3 months. The primary outcome was falls and the secondary outcome was all-cause mortality. Results: A total of 26 participants were enrolled in the study. The study group consisted of 13 residents who had a fall detection device in their rooms. The remaining 13 residents on the same floor formed the control group. Participants had a mean age of 82 ± 10 years and 89% of the residents were female. The most prevalent comorbidity was dementia. Two residents from the control group and one resident from the study group experienced a fall event during follow-up. The fall events in the control group were identified retrospectively by the nursing home staff, whereas the fall in the study group received a prompt response from the staff who were notified by the alarm. One resident was transferred to the hospital and died due to a non-fall related reason. Conclusion: Device technology may provide an opportunity for timely intervention to prevent fall-related morbidity in institutionalized older adults.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Psikiyatri; GERONTOLOJİ; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; PSYCHIATRY; GERONTOLOGY; GERIATRICS & GERONTOLOGY; Gerontoloji; Geriatri ve Gerontoloji; Psikiyatri ve Ruh Sağlığı; Gerontology; Geriatrics and Gerontology; Psychiatry and Mental Health; fall detection device; falls; nursing home; older adults